Website Pencari Produk Terlaris untuk Membantu Penjualan Pada Toko Online - Setiono, Audrey; Rostianingsih, Silvia; Purbowo, Anita Nathania (Jurnal Infra, 2018)
Development of technologies become a positive impact for people who want to open new business opportunities by selling their products online. The obstacle is in the selection of products that will be sold, people tend to have a hard time deciding the product that they needed because they don't know what products are on demand in the market. In order to facilitate users who want to know the current best-selling products, website by using Web Scraping method is made as a support to collect information about the best-selling products contained in the marketplace of Tokopedia, Shopee and Bukalapak. The informations include name of the goods, price of the goods, number of products sold, product image and origin of the site. In conclusion, the website can help users finding the best selling products according to the categories selected.